Could the AfD be banned from participating in German elections? - Hansen, Michael A. (London School of Economics and Political Science, 2026)
There have been calls to ban the Alternative for Germany (AfD) from participating in German elections following revelations about an alleged plan involving members of the party to implement mass deportations. Michael A. Hansen examines whether the party could really be banned and what the consequences of such a ruling might be for German politics.